2010
DOI: 10.1073/pnas.1001198107
|View full text |Cite
|
Sign up to set email alerts
|

Activation of dormant ovarian follicles to generate mature eggs

Abstract: Although multiple follicles are present in mammalian ovaries, most of them remain dormant for years or decades. During reproductive life, some follicles are activated for development. Genetically modified mouse models with oocyte-specific deletion of genes in the PTEN-PI3K-Akt-Foxo3 pathway exhibited premature activation of all dormant follicles. Using an inhibitor of the Phosphatase with TENsin homology deleted in chromosome 10 (PTEN) phosphatase and a PI3K activating peptide, we found that short-term treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
340
2
10

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 374 publications
(365 citation statements)
references
References 43 publications
(45 reference statements)
4
340
2
10
Order By: Relevance
“…Our earlier report demonstrated the ability of Akt stimulators to activate dormant primordial follicles (14). We now demonstrated additive increases in follicle growth when ovarian fragments containing secondary and smaller follicles were treated with Akt stimulators.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…Our earlier report demonstrated the ability of Akt stimulators to activate dormant primordial follicles (14). We now demonstrated additive increases in follicle growth when ovarian fragments containing secondary and smaller follicles were treated with Akt stimulators.…”
mentioning
confidence: 70%
“…Similar to normal menstrual cycles, usually only one follicle emerged from the growing pool to reach the preovulatory stage. Although earlier data indicated that 6 mo are needed for the development of human primordial follicles to the preovulatory stage (14,19), all eight patients developed preovulatory follicles (∼2 cm) in less than 6 mo of grafting, with some of them (patients 1, 3, 5, and 7) developing preovulatory follicles within 3 wk, indicating rapid growth of secondary follicles. In contrast, preovulatory follicles developed after 6 mo of grafting were likely derived from primordial follicles.…”
Section: Additive Effects Of Hippo Signaling Disruption and Akt Stimumentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Akt pathway stimulation using pharmacological PTEN inhibitors has been shown to drive primordial follicle activation of human ovarian cortical tissue that was xenotransplanted into immunodeficient mice [77]. Moreover, a similar follicle activation protocol resulted in a human live birth in a patient with primary ovarian insufficiency [78].…”
Section: Discussionmentioning
confidence: 99%
“…In mice, the oocyte-specific deletion of Pten (phosphatase and tensin homolog deleted on chromosome 10), which negatively regulates the action of PI3K, causes excessive activation of primordial follicles [19,20]. Li et al [21] treated human ovarian fragments and mouse ovaries with a PTEN inhibitor and transplanted them to SCID mice. After transplantation, increased numbers of antral follicles were obtained from inhibitor-treated groups than the control.…”
Section: Discussionmentioning
confidence: 99%